Pengukuran Ketinggian Permukaan Air Sungai menggunakan Prinsip Tekanan Berbasis Mikrokontroler ATMega328: Bachtera Indarto, Hasto Sunarno, Muhammad Fahrudin, Didiek B. Rahmat - Bachtera Indarto, Bachtera Indarto; Hasto Sunarno, Hasto Sunarno; Muhammad Fahrudin, Muhammad Fahrudin; Didiek Basuki Rachmad, Didiek Basuki Rachmad (Jurnal Fisika dan Aplikasinya, 2025)
Measuring tools water level of theriver using ATmega328 microcontroller-based pressure principle has been made. The amount of water level proportional to the pressure in the water is converted into pressure transmitter using a pipe in which there is a pressure sensor BMP085. Data were processed using ATMega382 microcontroller, which is then displayed on a liquid crystal display (LCD) 16 × 2. Based on the research that has been done, the transmitter pipe can be used to measure the height of the water surface by using the principle of pressure. BMP085 pressure sensor and transmitter that is designed pipe is able to be used properly with based on the calibration factors: Level = (11.52 × pressure - 11612) mm.. When testing the system, the water level in the tidal riversluiceWonorejo, Surabaya can be observed by a correction factor: Level = (11.47 × pressure - 10149) mm.